En kustnära näring navigerar: Styrning och kustnära yrkesfiske i den tjänsteinriktade ekonomin - Andersson, Malin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
The traditional industry of inshore commercial fisheries is in a state of transformation, which manifests itself in the fisheries management, in harbors and within the community of fishermen. With the help of discourse theory and the concept of positioning, an ethnographic material of documents, observations, interviews and news articles generated between 2011-2015 is analyzed. The aim is to explore how the inshore commercial fishery is formed and negotiated in the service economy. This article finds contradictory discourses formed in the relationship between fisheries management and fishermen, where the commercial fisheries are extensively regulated by the state authorities. At the same time the fishermen are encouraged to engage in governance projects and to become entrepreneurs. The fishermen describe their work-life and how they started working in the tourism industry, stories which positions the inshore commercial fishery and the fishermen themselves as entrepreneurs with ecological knowledge and long-term responsibilities. The findings suggest a lack of trust in the context of fisheries governance.